A double-gradient low-loading membrane electrode and a preparation method and application thereof

CN122889795APending Publication Date: 2026-10-09SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611404512.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

但是现有技术中的AEMFC阳极,往往存在低PtRu载量和高电流密度运行条件下面临的水淹、H2传输受阻、OH-传导界面接触不足以及贵金属空间利用效率不高等问题

Benefits of technology

本发明面向AEMFC阳极特有反应环境建立了一种“双梯度协同结构”,一方面,阳极发生氢气氧化反应并生成水,且OH-由阴极经膜向阳极迁移,高电流密度下阳极更易发生水淹和H2传输受限;另一方面,靠近阴离子交换膜一侧具有更充分的OH-传导和更高反应位点利用率,而靠近微孔层侧更主要承担H2供应和水分排出功能。为此,本发明在气体扩散基底表面构建梯度孔结构微孔层,梯度孔结构微孔层包括由下至上依次设置的第一微孔层和第二微孔层,由下至上方向的微孔层的孔径和/或孔隙率依次减小,靠近气体扩散基底侧形成较高孔隙率和连续排水通道,有利于阳极生成水向气体扩散基底方向排出;靠近催化层侧形成相对致密且支撑性更好的结构,有利于改善催化层/微孔层界面接触并避免催化层塌陷或局部脱落,用于协同提高阳极排水能力、H2供应能力和催化层支撑性;同时在该梯度微孔层表面构建由低PtRu含量向高PtRu含量逐层过渡的梯度载量催化层,低PtRu含量催化子层设置于靠近微孔层侧,高PtRu含量催化子层设置于靠近阴离子交换膜侧,使PtRu优先分布于靠近阴离子交换膜的高利用率区域。该结构能够在显著降低阳极PtRu总载量的同时保持较高峰值功率密度和极限电流密度。因此,通过梯度孔结构微孔层和梯度PtRu 载量的“双梯度协同结构”显著降低阳极贵金属载量的同时保持高功率输出。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889795A_ABST
    Figure CN122889795A_ABST
Patent Text Reader

Abstract

The application discloses a double-gradient low-loading membrane electrode and a preparation method and application thereof, and relates to the technical field of new energy sources.The double-gradient low-loading membrane electrode comprises, from bottom to top, a gas diffusion substrate, a gradient-pore-structure microporous layer and a gradient PtRu-loading catalytic layer; and the application further provides an electrode assembly comprising the double-gradient low-loading membrane electrode.The application constructs a gradient-pore-structure microporous layer induced by a pore-forming agent on the surface of the gas diffusion substrate, which is used for cooperatively improving the anode drainage capacity, H2 supply capacity and catalytic layer supportability; meanwhile, the gradient-loading catalytic layer is constructed on the surface of the gradient microporous layer, which is gradually transitioned from low PtRu content to high PtRu content, so that the PtRu is preferentially distributed in the high-utilization-area close to the anion exchange membrane.The structure can significantly reduce the total loading of the anode PtRu while maintaining a high peak power density and a limit current density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new energy technology, specifically to a dual-gradient low-load film electrode, its preparation method, and its application. Background Technology

[0002] Alkaline membrane fuel cells (AEMFCs) use anion exchange membranes as solid electrolytes and hydroxide ions as the primary charge carriers. They offer advantages such as the ability to use low-precious metal or non-precious metal catalysts, lower corrosion resistance requirements for system components, and lower potential costs, making them an important direction for cost reduction in fuel cells. The membrane electrode assembly (MEA) is the core component of an AEMFC. The anode electrode typically consists of a gas diffusion substrate, a microporous layer, and a catalyst layer, and its structure directly affects H2 transport, electron conduction, and OH- ion exchange. - Conductivity, water generation and discharge, and PtRu catalyst utilization.

[0003] Existing Alkaline Membrane Fuel Cells (AEMFCs) mainly consist of a low-noble-metal-loading alkaline membrane fuel cell anode, a gas diffusion electrode with a microporous layer, and a multilayer or gradient catalyst layer electrode. Current anode electrodes typically use carbon paper or carbon cloth as the gas diffusion substrate, with a microporous layer composed of conductive carbon materials and a hydrophobic binder fabricated on its surface, followed by a catalyst layer loaded onto the microporous layer. Commonly used materials for the microporous layer include carbon black, acetylene black, Vulcan carbon, graphitized carbon materials, carbon nanotubes, and polytetrafluoroethylene (PTFE). Carbon materials are used to construct the electron conduction network and pore structure framework, while hydrophobic components such as PTFE are used to adjust the electrode's hydrophobicity and promote water removal. The catalyst layer is usually prepared from platinum / ruthenium / carbon, platinum / carbon, or other low-noble-metal catalysts, anion exchange ionomers, and solvents. The catalyst provides active sites for the hydrogen oxidation reaction, and the ionomer is used to construct hydroxide ion conduction channels and enhance the bonding between the catalyst layer and the membrane. However, existing AEMFC anodes often face challenges such as flooding, H2 transport obstruction, and OH- ionization under low PtRu loading and high current density operating conditions. - Problems include insufficient contact at the conductive interface and low space utilization efficiency of precious metals. Summary of the Invention

[0004] The purpose of this invention is to at least solve one of the technical problems existing in the prior art, and to provide a dual-gradient low-load membrane electrode, its preparation method and application, specifically a dual-gradient low-load membrane electrode for the anode of an alkaline membrane fuel cell, its preparation method and its application in an alkaline membrane fuel cell.

[0005] The technical solution of the present invention is as follows: In a first aspect, the present invention provides a dual-gradient low-loading membrane electrode, the dual-gradient low-loading membrane electrode comprising, from bottom to top, a gas diffusion substrate, a gradient pore structure microporous layer and a gradient PtRu loading catalytic layer; The gradient pore structure microporous layer includes a first microporous layer and a second microporous layer arranged sequentially from bottom to top, wherein the pore size in the first microporous layer is larger than the pore size in the second microporous layer, and / or the porosity in the first microporous layer is higher than the porosity in the second microporous layer. The gradient PtRu loading catalyst layer includes a first catalyst layer and a second catalyst layer arranged sequentially from bottom to top, wherein the PtRu content in the first catalyst layer is less than the PtRu content in the second catalyst layer.

[0006] Optionally, both the first microporous layer and the second microporous layer include conductive carbon material and a pore-forming agent, wherein the mass ratio of the pore-forming agent to the conductive carbon material in the first microporous layer is greater than the mass ratio of the pore-forming agent to the conductive carbon material in the second microporous layer.

[0007] Optionally, the mass ratio of pore-forming agent to conductive carbon material in the first microporous layer is 80% to 150%. And / or, the mass ratio of pore-forming agent to conductive carbon material in the second microporous layer is 20%~80%; And / or, the conductive carbon material includes at least one of Vulcan XC-72R, acetylene black, graphitized carbon, carbon nanotubes, or graphene; And / or, both the first microporous layer and the second microporous layer further include a hydrophobic binder; And / or, the hydrophobic adhesive includes at least one of PTFE, PVDF or FEP; And / or, the pore-forming agent includes PEG-200, PEG-400, or a combination thereof.

[0008] Optionally, both the first catalyst layer and the second catalyst layer include a PtRu / C catalyst and anion exchange ionomer, and the mass fraction of PtRu in the first catalyst layer is less than the mass fraction of PtRu in the second catalyst layer. The mass fraction of PtRu in the first catalyst layer is 10%~30%, and the mass fraction of PtRu in the second catalyst layer is 30%~60%.

[0009] Optionally, the gradient PtRu loading catalyst layer further includes a third catalyst layer, wherein the first catalyst layer, the second catalyst layer and the third catalyst layer are arranged sequentially from bottom to top, and the PtRu content in the first catalyst layer, the PtRu content in the second catalyst layer and the PtRu content in the third catalyst layer increase sequentially. The mass fraction of PtRu in the first catalyst layer is 10%~20%, the mass fraction of PtRu in the second catalyst layer is 20%~30%, and the mass fraction of PtRu in the third catalyst layer is 30%~60%.

[0010] Optionally, the gradient PtRu loading catalyst layer further includes a third catalyst layer and a fourth catalyst layer, wherein the first catalyst layer, the second catalyst layer, the third catalyst layer and the fourth catalyst layer are arranged sequentially from bottom to top, and the PtRu content in the first catalyst layer, the PtRu content in the second catalyst layer, the PtRu content in the third catalyst layer and the fourth catalyst layer increases sequentially. The mass fraction of PtRu in the first catalyst layer is 10%~20%, the mass fraction of PtRu in the second catalyst layer is 20%~30%, the mass fraction of PtRu in the third catalyst layer is 30%~40%, and the mass fraction of PtRu in the fourth catalyst layer is 40%~60%.

[0011] Optionally, in the gradient PtRu loading catalyst layer, the total PtRu loading is 0.05 mg·cm³. -2 ~0.60 mg·cm -2 .

[0012] Secondly, the present invention provides a method for preparing the aforementioned dual-gradient low-loading film electrode, comprising the following steps: Conductive carbon material, hydrophobic binder, pore-forming agent and solvent are mixed to prepare at least two microporous layer slurries with different mass ratios of pore-forming agent / conductive carbon material; A microporous layer slurry with the highest mass ratio of pore-forming agent to conductive carbon material is coated onto the surface of a gas diffusion substrate and dried to form a first microporous layer; another microporous layer slurry is coated onto the surface of the first microporous layer and dried to form a second microporous layer; the pore-forming agent is removed by heating in an inert atmosphere to form a gradient pore structure microporous layer. PtRu / C catalyst, anion exchange polymer and solvent are mixed to prepare at least two catalyst slurries with different PtRu contents; The catalyst slurry is sprayed layer by layer onto the surface of the gradient pore structure microporous layer in order of increasing PtRu mass fraction, and then dried to form a gradient PtRu loading catalyst layer, thus obtaining the dual-gradient low-loading membrane electrode.

[0013] Optionally, the method of removing the pore-forming agent by heating in an inert atmosphere includes: heat treatment at 300°C to 400°C in an inert atmosphere for 0.1 h to 10 h.

[0014] Thirdly, the present invention provides a membrane electrode assembly, including an anode electrode, an anion exchange membrane and a cathode electrode, wherein the anode electrode is the dual-gradient low-load membrane electrode.

[0015] Fourthly, the present invention provides a fuel cell including the aforementioned membrane electrode assembly.

[0016] This invention has at least one of the following beneficial effects: This invention establishes a "dual-gradient synergistic structure" for the unique reaction environment of AEMFC anodes. On one hand, hydrogen oxidation occurs at the anode to generate water, and OH... - From the cathode to the anode, under high current density, the anode is more prone to flooding and H2 transport is restricted; on the other hand, the side closer to the anion exchange membrane has more abundant OH-. - To improve conductivity and higher reaction site utilization, the side closer to the microporous layer primarily serves the functions of H2 supply and water removal. Therefore, this invention constructs a gradient pore structure microporous layer on the surface of a gas diffusion substrate. This gradient pore structure microporous layer includes a first microporous layer and a second microporous layer arranged sequentially from bottom to top. The pore size and / or porosity of the microporous layers decrease sequentially from bottom to top. The side closer to the gas diffusion substrate forms a higher porosity and continuous drainage channels, facilitating the discharge of anode-generated water towards the gas diffusion substrate. The side closer to the catalyst layer forms a relatively dense and more supportive structure, which helps improve the catalyst layer / microporous layer interface contact and prevents catalyst layer collapse or local detachment, thus synergistically improving anode drainage capacity, H2 supply capacity, and catalyst layer support. Simultaneously, a gradient loading catalyst layer is constructed on the surface of this gradient microporous layer, transitioning from low PtRu content to high PtRu content. The low PtRu content catalyst sublayer is located near the microporous layer, and the high PtRu content catalyst sublayer is located near the anion exchange membrane, allowing PtRu to preferentially distribute in the high-utilization region near the anion exchange membrane. This structure can maintain high peak power density and limiting current density while significantly reducing the total PtRu loading of the anode. Therefore, the "dual-gradient synergistic structure" of gradient-pore microporous layer and gradient PtRu loading significantly reduces the noble metal loading of the anode while maintaining high power output. Attached Figure Description

[0017] Figure 1 These are comparison diagrams of the membrane electrode polarization curves obtained from Examples 1-3 and Comparative Examples 1-2 of the present invention; wherein, MPL-0 corresponds to Comparative Example 1, PEG-0 corresponds to Comparative Example 2, PEG-50 corresponds to Example 1, PEG-100 corresponds to Example 2, and PEG-100 / 50 corresponds to Example 3.

[0018] Figure 2 The figures show the anode electrode performance of the alkaline membrane fuel cell based on a microporous layer with a gradient pore structure obtained in Examples 3-8 of this invention; wherein, (a) in the figure is Example 3 (0.6 mg·cm⁻¹) -2 PtRu-60wt%), Example 4 (0.4mg·cm -2 PtRu-60wt%), Example 5 (0.2mg·cm -2The performance of the anode electrode of an alkaline membrane fuel cell based on a microporous layer with a gradient pore structure was obtained by PtRu-60wt%; Figure (b) shows the performance of Example 5 (0.2 mg·cm⁻¹). -2 PtRu-60wt%), Example 6 (0.2mg·cm -2 PtRu-10% / PtRu-60%), Example 7 (0.2 mg·cm⁻¹) -2 PtRu-10% / PtRu-20% / PtRu-60%), Example 8 (0.1 mg·cm⁻¹) -2 The performance of the anode electrode of an alkaline membrane fuel cell based on a microporous layer with a gradient pore structure was obtained by (PtRu-10% / PtRu-20% / PtRu-30% / PtRu-60%).

[0019] Figure 3 This is the performance of the alkaline membrane fuel cell anode electrode based on MPL-0 obtained in Comparative Example 1 of the present invention; wherein, (a) in the figure shows the performance of the anode electrode of Comparative Example 1 after spraying with 0.6 mg·cm⁻¹. -2 0.4 mg·cm -2 and 0.2 mg·cm -2 The anode catalyst layer was prepared using PtRu-60wt% catalyst slurry; Figure (b) shows the 0.2 mg·cm⁻¹ anolyte layer sprayed in Comparative Example 1. -2 PtRu-60%, 0.2 mg·cm - 2 PtRu-10% / PtRu-60%, 0.2 mg·cm -2 PtRu-10% / PtRu-20% / PtRu-60% and 0.1mg·cm -2 Anode catalyst layers were prepared using PtRu-10% / PtRu-20% / PtRu-30% / PtRu-60% catalyst slurry.

[0020] Figure 4 The figure shows the performance of the alkaline membrane fuel cell anode electrode based on the MPL-XC-72R microporous layer obtained in Comparative Example 2 of this invention; wherein, (a) in the figure shows the performance of the anode electrode of Comparative Example 2 after spraying with 0.6 mg·cm⁻¹. -2 0.4 mg·cm -2 and 0.2 mg·cm -2 The anode catalyst layer was prepared using PtRu-60wt% catalyst slurry; Figure (b) shows Comparative Example 2, where 0.2 mg·cm⁻¹ catalyst was sprayed onto the anode. -2 PtRu-60%, 0.2 mg·cm -2 PtRu-10% / PtRu-60%, 0.2 mg·cm -2 PtRu-10% / PtRu-20% / PtRu-60% and 0.1mg·cm- 2 Anode catalyst layers were prepared using PtRu-10% / PtRu-20% / PtRu-30% / PtRu-60% catalyst slurry.

[0021] Figure 5 These are membrane electrode impedance diagrams obtained with different PEG addition amounts from Examples 1-3 and Comparative Examples 1-2 of the present invention; wherein, MPL-0 corresponds to the coating of 0.6 mg·cm⁻¹ in Comparative Example 1. -2 Anode catalyst layer was prepared using PtRu-60wt% catalyst slurry; PEG-0 corresponds to Example 2, PEG-50 corresponds to Example 1, PEG-100 corresponds to Example 2, and PEG-50 / 100 corresponds to Example 3.

[0022] Figure 6 These are electrochemical activity area test graphs of membrane electrodes with different loadings obtained in Examples 4-7 of the present invention; wherein, (a) in the figure is an electrochemical activity area test graph; and (b) in the figure is an electrochemical activity area bar graph.

[0023] Figure 7 These are SEM images of membrane electrodes with different PEG contents obtained in Examples 1-3 and Comparative Example 2 of the present invention; wherein, XC72R corresponds to Comparative Example 2, PEG-100 / 50 corresponds to Example 3, PEG-50 corresponds to Example 1, and PEG-100 corresponds to Example 2. Detailed Implementation

[0024] To make the technical problems solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.

[0025] To address the aforementioned technical issues, the applicant conducted a search of existing technologies. The search revealed that the closest prior art falls into two main categories: The first category is Chinese Patent CN1658422A, which discloses a gas diffusion layer for fuel cells and its preparation method. The core of this method lies in setting a microporous layer on the side of a porous substrate near the catalyst layer, and forming gradient pores with a trapezoidal longitudinal cross-section through a pore-forming dosage gradient. This results in the pore diameter at one end near the porous substrate being larger than that at the other end, thereby utilizing the gradient pore structure to promote water discharge and improve fuel cell performance. The technical focus of this solution is on the gradient pore structure of the gas diffusion layer / microporous layer itself, and it does not address the OH- ions on the anode water production side of an alkaline membrane fuel cell. -The coupling relationship between conduction, H2 transport, and precious metal space utilization is not disclosed, nor is the further matching of a gradient PtRu loading catalyst layer on the surface of the gradient microporous layer. The second type is Chinese patent CN109065894A, which discloses a three-dimensional gradient structure anode for a membrane-free, oxygen-free direct methanol fuel cell. It uses PtRuM / C catalysts with different metal loadings gradient-coated on the anode diffusion layer, allowing methanol fuel to react gradually along the depth of the electrode, reducing methanol permeation and improving methanol utilization. This scheme belongs to the direct methanol fuel cell system. The core technical problem is the mixing potential caused by high-concentration methanol fuel penetrating the electrolyte. Its gradient structure serves to consume methanol and suppress methanol cross-permeation, not to address the issues of water generation discharge, H2 diffusion, and OH- in the hydrogen anode of an AEMFC. - Issues related to the contact at the conductive interface and the space utilization of active sites under low PtRu loading.

[0026] However, the aforementioned existing technologies have not fully addressed the following issues: First, conventional microporous layers have a uniform pore structure, or only emphasize the pore size gradient itself, making it difficult to simultaneously consider the drainage capacity near the carbon paper side and the structural support / interface contact near the catalyst layer side; Second, conventional low-load anodes typically reduce the overall PtRu content, resulting in insufficient active sites in the high-utilization region on the membrane side, while the utilization rate of precious metals in regions far from the membrane side is low; Third, existing gradient catalyst layer designs are mostly designed for PEMFC cathode ORR, PEM electrolyzers, or direct methanol fuel cells, and are not designed for AEMFC anode water production, H2 transport, and OH... - The direction of conduction is matched collaboratively.

[0027] Therefore, after extensive research and experimentation, this invention proposes a low-load dual-gradient membrane electrode suitable for the anode of alkaline membrane fuel cells.

[0028] This invention addresses the challenges faced by existing AEMFC anodes under low PtRu loading and high current density operating conditions, including flooding, H2 transport obstruction, and OH... - To address issues such as insufficient conductive interface contact and low space utilization efficiency of precious metals, this invention proposes a low-loading anode electrode and its preparation method that synergistically matches a "gradient pore structure microporous layer + gradient PtRu loading catalyst layer". Unlike existing single-gradient microporous layer or single-gradient catalyst coating, the key to this invention lies in utilizing functional partitioning along the thickness direction of the AEMFC anode to couple the drainage / support function of the microporous layer with the reaction site / ion conduction function of the catalyst layer.

[0029] An embodiment of the present invention provides a dual-gradient low-loading membrane electrode, which includes a gas diffusion substrate, a gradient pore structure microporous layer and a gradient PtRu loading catalyst layer arranged sequentially from bottom to top; The gradient pore structure microporous layer includes a first microporous layer and a second microporous layer arranged sequentially from bottom to top, wherein the pore size in the first microporous layer is larger than the pore size in the second microporous layer, and / or the porosity in the first microporous layer is higher than the porosity in the second microporous layer. The gradient PtRu loading catalyst layer includes a first catalyst layer and a second catalyst layer arranged sequentially from bottom to top, and the PtRu content in the first catalyst layer is less than the PtRu content in the second catalyst layer.

[0030] This invention proposes a low-loading anode electrode with a synergistic matching of a "gradient pore structure microporous layer + gradient PtRu loading catalyst layer". On the one hand, by forming a gradient in pore size, porosity, and pore connectivity along the thickness direction, a higher porosity and continuous drainage channel are formed near the gas diffusion substrate, which is beneficial for the discharge of anode-generated water towards the gas diffusion substrate. A relatively dense and more supportive structure is formed near the catalyst layer, which is beneficial for improving the catalyst layer / microporous layer interface contact and avoiding catalyst layer collapse or local detachment. On the other hand, a low PtRu content catalyst sublayer is set near the microporous layer to reduce the consumption of precious metals in the low-utilization region far from the membrane side and maintain the gas / water transport channel; a high PtRu content catalyst sublayer is set near the anion exchange membrane to increase the reaction site density and OH content in the high-utilization region of the membrane side. - Conductive contact; the intermediate PtRu content catalyst sublayer serves as a continuous transition for forming reaction sites and transport channels. Through the combined effect of these two aspects, high power output is maintained while significantly reducing the noble metal loading of the anode, demonstrating a significant synergistic effect.

[0031] In some embodiments, both the first microporous layer and the second microporous layer include conductive carbon material, hydrophobic binder, and pore-forming agent, wherein the mass ratio of pore-forming agent to conductive carbon material in the first microporous layer is greater than the mass ratio of pore-forming agent to conductive carbon material in the second microporous layer.

[0032] In some embodiments, the mass ratio of pore-forming agent to conductive carbon material in the first microporous layer is 80% to 150%; preferably 80% to 120%, more preferably 100%.

[0033] The mass ratio of pore-forming agent to conductive carbon material in the second microporous layer is 20% to 80%; preferably 40% to 60%; more preferably 50%.

[0034] The high PEG content layer near the carbon paper side forms a higher porosity and continuous drainage channels, which is conducive to the discharge of anode-generated water towards the gas diffusion substrate; the low PEG content layer near the catalyst layer side forms a relatively dense and more supportive structure, which is conducive to improving the contact between the catalyst layer / microporous layer interface and avoiding catalyst layer collapse or local detachment.

[0035] The conductive carbon material includes at least one of Vulcan XC-72R, acetylene black, graphitized carbon, carbon nanotubes, or graphene; preferably Vulcan XC-72R.

[0036] The hydrophobic adhesive includes at least one of PTFE, PVDF or FEP; preferably PTFE.

[0037] The pore-forming agent includes PEG-200, PEG-400, or a combination thereof.

[0038] The microporous layer consists of two or more microporous sublayers. The mass ratio of PEG to conductive carbon material varies in different microporous sublayers. After PEG is removed by drying and inert atmosphere heat treatment, a gradient of pore size, porosity and pore connectivity is formed in the thickness direction.

[0039] Optionally, both the first catalyst layer and the second catalyst layer include a PtRu / C catalyst and anion exchange ionomer, and the mass fraction of PtRu in the first catalyst layer is less than the mass fraction of PtRu in the second catalyst layer. The mass fraction of PtRu in the first catalyst layer is 10%~30%, and the mass fraction of PtRu in the second catalyst layer is 30%~60%.

[0040] In some embodiments, the gradient PtRu loading catalyst layer includes a first catalyst layer, a second catalyst layer, and a third catalyst layer arranged sequentially from bottom to top, wherein the PtRu content in the first catalyst layer, the PtRu content in the second catalyst layer, and the PtRu content in the third catalyst layer increase sequentially. The mass fraction of PtRu in the first catalyst layer is 10%~20%, the mass fraction of PtRu in the second catalyst layer is 20%~30%, and the mass fraction of PtRu in the third catalyst layer is 30%~60%.

[0041] In some embodiments, the gradient PtRu loading catalyst layer includes a first catalyst layer, a second catalyst layer, a third catalyst layer and a fourth catalyst layer arranged sequentially from bottom to top, and the PtRu content in the first catalyst layer, the PtRu content in the second catalyst layer, and the PtRu content in the third catalyst layer and the fourth catalyst layer increases sequentially. The mass fraction of PtRu in the first catalyst layer is 10%~20%, the mass fraction of PtRu in the second catalyst layer is 20%~30%, the mass fraction of PtRu in the third catalyst layer is 30%~40%, and the mass fraction of PtRu in the fourth catalyst layer is 40%~60%.

[0042] The gradient PtRu-supported catalyst layer comprises PtRu / C catalysts with different PtRu contents and anion exchange ionomers. The PtRu / C catalysts include at least two types of PtRu / C catalysts with PtRu mass fractions of 10%, 20%, 30%, and 60%, respectively designated as PtRu-10%, PtRu-20%, PtRu-30%, and PtRu-60%. The anion exchange ionomers include at least one type of piperidinium, quaternary ammonium, imidazolium, or other anion exchange ionomers for AEMFCs, preferably Versogen PiperIONA5 HCO3 type ionomers.

[0043] The gradient PtRu loading catalyst layer consists of two or more catalyst sublayers, with the PtRu content or noble metal distribution density gradually increasing from the side near the gradient micropore layer to the side near the anion exchange membrane. Preferred structures include a PtRu-10% / PtRu-60% bilayer structure, a PtRu-10% / PtRu-20% / PtRu-60% trilayer structure, or a PtRu-10% / PtRu-20% / PtRu-30% / PtRu-60% quadlayer structure. The low PtRu content catalyst sublayer is positioned near the micropore layer to reduce noble metal consumption in low-utilization regions far from the membrane side and to maintain gas / water transport channels; the high PtRu content catalyst sublayer is positioned near the anion exchange membrane side to increase the reaction site density and OH content in high-utilization regions on the membrane side. - Conductive contact; the intermediate PtRu content catalytic sublayer serves to form a continuous transition between reaction sites and transport channels.

[0044] In some embodiments, the total PtRu loading in the gradient PtRu-loaded catalyst layer is 0.05 mg·cm³. -2 ~0.60 mg·cm -2 .

[0045] The total loading of PtRu noble metal in the anode catalyst layer is 0.05 mg·cm³. -2 ~0.60 mg·cm -2 Preferably 0.10 mg·cm -2 ~0.40 mg·cm -2 More preferably 0.20 mg·cm -2 Furthermore, under a four-layer gradient structure, the total loading of PtRu noble metal in the anode catalyst layer can be reduced to 0.10 mg·cm⁻¹. -2 And it still maintains high battery output performance.

[0046] Another embodiment of the present invention provides a method for preparing the aforementioned dual-gradient low-loading film electrode, comprising the following steps: Conductive carbon material, hydrophobic binder, pore-forming agent and solvent are mixed to prepare at least two microporous layer slurries with different mass ratios of pore-forming agent / conductive carbon material; A microporous layer slurry with the highest mass ratio of pore-forming agent to conductive carbon material is coated onto the surface of a gas diffusion substrate and dried to form a first microporous layer; another microporous layer slurry is coated onto the surface of the first microporous layer and dried to form a second microporous layer; the pore-forming agent is removed by heating in an inert atmosphere to form a gradient pore structure microporous layer. PtRu / C catalyst, anion exchange polymer and solvent are mixed to prepare at least two catalyst slurries with different PtRu contents; The catalyst slurry is sprayed layer by layer onto the surface of the gradient pore structure microporous layer in order of increasing PtRu mass fraction, and then dried to form a gradient PtRu loading catalyst layer, thus obtaining the dual-gradient low-loading membrane electrode.

[0047] The preparation method of the present invention is simple and practical. By constructing a gradient pore structure microporous layer induced by a pore-forming agent on the surface of a gas diffusion substrate, and simultaneously constructing a gradient loading catalyst layer that transitions from low PtRu content to high PtRu content layer by layer on the surface of the gradient microporous layer, it is possible to maintain a high peak power density and limiting current density while significantly reducing the total PtRu loading of the anode.

[0048] In some embodiments, the preparation method includes: selecting a gas diffusion substrate; preparing microporous layer slurries containing different PEG contents and coating them layer by layer onto the surface of the gas diffusion substrate; drying at 60°C to 100°C, and then heat-treating at 300°C to 400°C for 0.1 h to 10 h in a nitrogen, argon, or other inert atmosphere, preferably at 350°C for 0.5 h to 3 h in a nitrogen atmosphere, to remove PEG and form a gradient pore structure microporous layer; subsequently preparing catalyst layer slurries containing different PtRu contents and spraying them layer by layer onto the surface of the gradient pore structure microporous layer in order of increasing PtRu content, and drying to obtain a low-noble-metal gradient-loading anode electrode; finally assembling it with an anion exchange membrane and a cathode electrode to form an AEMFC membrane electrode.

[0049] Another embodiment of the present invention provides a membrane electrode assembly, including an anode electrode, an anion exchange membrane and a cathode electrode, wherein the anode electrode is the dual-gradient low-load membrane electrode.

[0050] This invention can maintain high power output while significantly reducing the noble metal loading of the anode, and has obvious synergistic effects.

[0051] Another embodiment of the present invention provides a fuel cell including the aforementioned membrane electrode assembly.

[0052] This invention can maintain high peak power density and limiting current density while significantly reducing the amount of precious metals loaded in the anode, which is beneficial for achieving high performance and low cost of the anode electrode in alkaline membrane fuel cells.

[0053] In summary, compared with Chinese Patent CN1658422A, this invention does not simply form gradient pores on the microporous layer of the gas diffusion layer. Instead, in the AEMFC anode application scenario, it synergistically matches the PEG-100% / 50% gradient pore structure microporous layer with the membrane-side enriched PtRu gradient loading catalyst layer to solve the problems of anode-generated water discharge, H2 transport, and effective reaction zone distribution under low PtRu loading.

[0054] Compared with Chinese Patent CN109065894A, this invention is not for use in membrane-free oxygen-free direct methanol fuel cells, nor is it for setting a PtRuM / C gradient along the methanol fuel consumption direction to suppress methanol permeation; this invention is used as the anode of a hydrogen / oxygen AEMFC, with H2 as the reactant and OH as the conductive ion. - The technical effect is to alleviate anode flooding and H2 mass transfer polarization, and to improve the effective utilization rate of PtRu near the membrane side.

[0055] Experimental results show that the present invention achieves the desired effect at 0.6 mg·cm⁻¹. -2 With PtRu noble metal loading in the anolyte catalyst layer, the peak power density of the PEG-100% / 50% gradient pore structure microporous layer electrode can reach approximately 2.30 W·cm⁻¹. -2 The limiting current density is approximately 6.10 A·cm. -2 It is significantly superior to the MPL-free and PEG-0 comparative examples; the PtRu noble metal loading in the anode catalyst layer is 0.2 mg·cm³. -2 Under low loading conditions, the peak power density of the PtRu-10% / PtRu-20% / PtRu-60% three-layer gradient catalyst layer can reach approximately 2.15 W·cm⁻¹. -2 It is significantly superior to a single PtRu-60% catalyst layer with the same loading; the PtRu noble metal loading in the anode catalyst layer is 0.1 mg·cm³. -2 Under these conditions, the four-layer gradient structure can still maintain approximately 1.83 W·cm⁻¹ -2 The peak power density is achieved. These results demonstrate that the present invention can maintain high power output while significantly reducing the anode noble metal loading, exhibiting a significant synergistic effect.

[0056] The present invention will be further described in detail below with reference to specific embodiments, but the present invention is not limited to the following specific embodiments.

[0057] Raw materials: The gas diffusion substrate is Toray TGP-H-060 (5% PTFE); the microporous layer conductive carbon material is Vulcan XC-72R; the hydrophobic binder is polytetrafluoroethylene; the pore-forming agent is polyethylene glycol, specifically including one or both of PEG-200 and PEG-400; the anode catalyst is a PtRu / C catalyst, specifically including PtRu / C catalysts with PtRu mass fractions of 10%, 20%, 30%, and 60%, respectively denoted as PtRu-10%, PtRu-20%, PtRu-30%, and PtRu-60%; the anode gradient catalyst layer is formed by spraying two or more of PtRu-10%, PtRu-20%, PtRu-30%, and PtRu-60% layer by layer from the microporous layer side to the anion exchange membrane side; the anion exchange ionomer is Versogen-PiperION A5, anion exchange ionomer for alkaline membrane fuel cells. HCO3; the anion exchange membrane is a Versogen A20 anion exchange membrane; the cathode catalyst is a 50% Pt / C catalyst with a Pt loading of 0.4 mg·cm³. -2 The slurry solvent includes one or more of deionized water, ethanol, and isopropanol; the heat treatment protective atmosphere is nitrogen.

[0058] Example 1: Based on a single microporous layer (PEG / C mass ratio of 50%) and a single catalyst layer (0.6 mg·cm⁻¹) -2 PtRu-60wt% anode electrode This embodiment prepares an anode electrode based on a microporous layer with a PEG / C mass ratio of 50% and a single catalyst layer (PtRu-60wt%), including the following steps: (1) Select carbon paper as the gas diffusion substrate, and use it after cutting, cleaning and drying.

[0059] (2) Weigh conductive carbon black (Vulcan XC-72R), PTFE emulsion, PEG-200, and an alcohol-water mixed solvent (isopropanol:water = 3:1, v / v) to prepare a microporous layer slurry. The mass ratio of PEG-200 to Vulcan XC-72R is 50%, and the mass fraction of PTFE emulsion in the microporous layer solid component is 6%. After ultrasonic dispersion and mechanical stirring, the slurry is coated onto the surface of carbon paper, dried, and placed in a tube furnace for heat treatment at 350 °C for 1 h under a nitrogen atmosphere to remove the PEG pore-forming agent, thereby obtaining a microporous layer with a PEG / C mass ratio of 50%.

[0060] (3) Subsequently, a certain amount of PtRu / C catalyst, anion exchange ionomer, and alcohol-water mixed solvent were weighed to prepare a PtRu-60 wt% catalyst slurry. The PtRu / C catalyst had a Pt to Ru mass ratio of 2:1 and a PtRu alloy mass fraction of 60 wt%; the anion exchange ionomer had a mass fraction of 5 wt%; and the alcohol-water mixed solvent was a mixture of isopropanol and water with a volume ratio of 3:1. Specifically, 0.03 g of PtRu-60 wt% catalyst powder was weighed, and 0.018 g of anion exchange ionomer solution with a mass fraction of 5 wt% and 15 mL of isopropanol / water mixed solvent (volume ratio 3:1) were added. After ultrasonic dispersion for 30-60 min, mechanical stirring was performed to form a uniform and stable catalyst slurry. The obtained PtRu-60 wt% catalyst slurry was uniformly sprayed onto the surface of the microporous layer with a PEG / C mass ratio of 50% prepared in step (2). By adjusting the solid content of the slurry, the number of spraying times, and the deposition amount, the total loading of PtRu noble metal in the anode catalyst layer was controlled to be 0.6 mg·cm³. -2 The anode electrode is obtained.

[0061] (4) The obtained anode electrode is assembled with an anion exchange membrane (Versogen A20) and a cathode electrode (Pt / C) to form a membrane electrode assembly, wherein the cathode Pt loading is 0.4 mg·cm³. -2 Single-cell tests were conducted under the conditions of 70 °C, 80% RH, hydrogen at the anode, oxygen at the cathode, and a back pressure of 50 kPa.

[0062] As shown in Table 1 and Figure 1 , Figure 5 , Figure 7 As shown, the test results indicate that the microporous layer with a PEG / C mass ratio of 50% can improve anode drainage and gas transport performance. Compared with the ordinary MPL structure without PEG pore-forming agent, the battery output performance in the high current density region is improved.

[0063] Example 2: Based on a single microporous layer (PEG / C mass ratio of 100%) and a single catalyst layer (0.6 mg·cm⁻¹) - 2 PtRu-60wt% anode electrode This embodiment is basically the same as Example 1, except that the mass ratio of PEG to VulcanXC-72R in the microporous layer slurry is 100%, and the mass fraction of PTFE emulsion in the solid components of the microporous layer is still 6%. After coating, drying, and heat treatment at 350 °C in a nitrogen atmosphere for 1 h, a microporous layer with a PEG / C mass ratio of 100% is obtained.

[0064] A PtRu-60wt% catalyst slurry was sprayed onto the surface of the microporous layer. By adjusting the catalyst slurry concentration, the number of sprays, and the deposition amount, the total PtRu noble metal loading in the anode catalyst layer was controlled to be 0.6 mg·cm³. -2 And conduct single-cell tests according to the above conditions.

[0065] As shown in Table 1 and Figure 1 , Figure 5 , Figure 7 As shown, the test results indicate that a microporous layer with a PEG / C mass ratio of 100% can further improve the porosity and drainage capacity of the microporous layer, thus improving anode moisture removal and hydrogen transport. However, if the entire microporous layer uses a high PEG content, the structure near the catalyst layer may become relatively loose, affecting catalyst layer support and interfacial contact. Therefore, while a single high-PEG content microporous layer is beneficial for drainage, its overall performance can still be further optimized through a gradient pore structure.

[0066] Example 3: Based on a gradient pore structure microporous layer (PEG / C mass ratio of 100% / 50%) and a single catalyst layer (0.6 mg·cm³). -2 PtRu-60wt% anode electrode This embodiment prepares an anode electrode based on a gradient pore structure microporous layer with a PEG / C mass ratio of 100% / 50% and a single catalyst layer (PtRu-60wt%), including the following steps: Two microporous layer slurries with PEG / C mass ratios of 100% and 50% were prepared according to the methods of Example 2 and Example 1, respectively. In each slurry, the mass fraction of PTFE emulsion in the microporous layer solid component was 6%.

[0067] First, a microporous layer slurry with a PEG / C mass ratio of 100% is coated onto the surface of carbon paper to form a high-porosity microporous sublayer near the carbon paper side. After drying, a microporous layer slurry with a PEG / C mass ratio of 50% is coated to form a relatively low-porosity microporous sublayer near the catalyst layer side. After coating, the layer is dried at 80 °C and then placed in a tube furnace for heat treatment at 350 °C for 1 h under a nitrogen atmosphere to remove the PEG-200 pore-forming agent, resulting in a microporous layer with a gradient pore structure.

[0068] In this gradient pore structure, the 100% PEG layer near the carbon paper side has high porosity and strong drainage capacity, which is beneficial for the discharge of anode moisture to the gas diffusion substrate; the 50% PEG layer near the catalyst layer side has relatively good structural support, which is beneficial for improving the interface contact between the catalyst layer and the microporous layer. Through the above two-layer gradient structure, the synergistic optimization of anode drainage capacity, hydrogen transport capacity and catalyst layer support can be achieved.

[0069] Subsequently, following the method of Example 1, a PtRu-60wt% catalyst slurry was sprayed onto the surface of the gradient pore structure microporous layer with a PEG / C mass ratio of 100% / 50%. By adjusting the catalyst slurry concentration, the number of spraying times, and the deposition amount, the total PtRu noble metal loading in the anode catalyst layer was controlled to be 0.6 mg·cm³. -2 An anode catalyst layer is formed. The resulting anode electrode is then assembled with a Versogen A20 anion exchange membrane and a cathode electrode to form a membrane electrode assembly, wherein the cathode Pt loading is 0.4 mg·cm³. -2 And test according to the single-cell conditions described above.

[0070] As shown in Table 1 and Figures 1-2 , Figure 5 , Figure 7 As shown, the test results indicate that, compared with uniform microporous layers with PEG / C mass ratios of 50% or 100%, the gradient pore structure microporous layer with a PEG / C mass ratio of 100% / 50% exhibits superior overall performance, significantly improving anode drainage capacity and hydrogen transport capacity under high current density while ensuring catalyst layer support.

[0071] Example 4: Based on a gradient pore structure microporous layer (PEG / C mass ratio of 100% / 50%) and a single catalyst layer (0.4 mg·cm³). -2 PtRu-60% anode electrode In this embodiment, a gradient pore microporous layer with a PEG / C mass ratio of 100% / 50% prepared in Example 3 was used as the anode support layer. A PtRu-60wt% catalyst slurry was sprayed onto its surface to form a low-noble-metal-loading anode catalyst layer. By adjusting the catalyst slurry concentration, the number of spraying passes, and the deposition amount, the total PtRu noble metal loading in the anode catalyst layer was controlled to be 0.4 mg·cm³. -2 .

[0072] The resulting anode electrode was assembled with a Versogen A20 anion exchange membrane and a cathode electrode to form a membrane electrode assembly, wherein the cathode Pt loading was 0.4 mg·cm³. -2 And test according to the single-cell conditions described above.

[0073] As shown in Table 1 and Figure 2 , Figure 6 As shown, the test results indicate that, based on a gradient pore structure microporous layer with a PEG / C mass ratio of 100% / 50%, the PtRu noble metal loading in the anode catalyst layer is reduced to 0.4 mg·cm³. -2 Even with these conditions, the battery still maintains high output performance. This result demonstrates that the gradient pore structure microporous layer can maintain good anode drainage capacity, hydrogen transport capacity, and catalyst layer utilization efficiency even with low noble metal loading.

[0074] Example 5: Based on a gradient pore structure microporous layer (PEG / C mass ratio of 100% / 50%) and a single catalyst layer (0.2 mg·cm³). -2 PtRu-60% anode electrode In this embodiment, the gradient pore structure microporous layer with a PEG / C mass ratio of 100% / 50% prepared in Example 3 was used as the anode support layer. PtRu-60% catalyst slurry was directly sprayed onto its surface to prepare a 0.2 mg·cm⁻¹ anode. -2 Low-loading anode electrode, i.e., the PtRu noble metal loading in the anode catalyst layer is reduced to 0.2 mg·cm⁻¹. -2 .

[0075] Specifically, a PtRu-60wt% catalyst slurry was prepared, comprising a PtRu-60wt% catalyst, anion exchange ionomer, and an isopropanol / water mixed solvent (volume ratio 3:1). Specifically, 0.03g of PtRu-60wt% catalyst powder was weighed, and 0.018g of a 5wt% anion exchange ionomer solution and 15mL of an isopropanol / water mixed solvent (volume ratio 3:1) were added. After ultrasonic dispersion for 30-60 min, mechanical stirring was performed to form a uniform and stable catalyst slurry. This catalyst slurry was uniformly sprayed onto the surface of a gradient pore structure microporous layer with a PEG / C mass ratio of 100% / 50% prepared in Example 3. By controlling the number of sprayings, slurry concentration, and deposition amount, the total PtRu noble metal loading in the anode catalyst layer was made to be 0.2 mg·cm³. -2 After spraying and drying, a 0.2 mg·cm³ microporous layer based on a gradient pore structure was obtained. -2 PtRu-60% low-load anode electrode.

[0076] The resulting anode electrode was assembled with a Versogen A20 anion exchange membrane and a cathode electrode to form a membrane electrode assembly, wherein the cathode Pt loading was 0.4 mg·cm³. -2 And test according to the single-cell conditions described above.

[0077] As shown in Table 1 and Figure 2 , Figure 6 As shown, the test results indicate that when a single PtRu-60% catalyst is used and the PtRu noble metal loading in the anode catalyst layer is reduced to 0.2 mg·cm⁻¹, the effect is significant. -2 At that time, the battery can still maintain a certain output performance, but compared to PtRu with a noble metal loading of 0.4 mg·cm³, it is significantly slower. -2The anode electrode exhibited decreased performance in the peak power density and high current density regions. This result indicates that simply reducing the noble metal loading reduces the number of effective reaction sites on the membrane side, leading to a decline in anode performance at low loading levels. Therefore, this example can serve as a performance reference for subsequent gradient loading catalytic layer electrodes, illustrating the effectiveness of different loading methods at the same 0.2 mg·cm⁻¹ temperature range. -2 With a total precious metal loading, a gradient loading catalyst layer can further improve the utilization efficiency of precious metals and the output performance of the battery.

[0078] Example 6: Based on a gradient pore structure microporous layer (PEG / C mass ratio of 100% / 50%) and a bilayer gradient catalytic layer (0.2 mg·cm³). -2 Anode electrode of PtRu-10% / PtRu-60% This embodiment is based on the gradient pore structure microporous layer with a PEG / C mass ratio of 100% / 50% prepared in Example 3, and prepares 0.2 mg·cm⁻¹ microporous layer. -2 Anode electrode with a double-layer gradient catalytic layer.

[0079] PtRu-10wt% and PtRu-60wt% catalyst slurries were prepared according to the method in Example 1. The PtRu-10wt% catalyst slurry was first sprayed onto the surface of the gradient pore structure microporous layer to form a low-PtRu content catalyst sublayer near the microporous layer; subsequently, the PtRu-60wt% catalyst slurry was sprayed to form a high-PtRu content catalyst sublayer near the anion exchange membrane. By controlling the spraying amount of the two layers, the total PtRu noble metal loading in the anode catalyst layer was achieved to be 0.2 mg·cm³. -2 .

[0080] The obtained anode electrode was assembled with the Versogen A20 anion exchange membrane and the cathode electrode to form a membrane electrode assembly, and tested according to the single cell conditions described above.

[0081] As shown in Table 1 and Figure 2 , Figure 6 As shown, the test results indicate that, as in Example 5, 0.2 mg·cm⁻¹ -2 Compared to a low-load anode electrode prepared with a single PtRu-60% catalyst, the PtRu-10% / PtRu-60% bilayer gradient catalyst layer exhibits higher peak power density and better high current density output performance. This result indicates that placing the catalyst with a higher PtRu content close to the anion exchange membrane side is beneficial for increasing the active site density and the utilization efficiency per unit of noble metal in the membrane-side reaction region.

[0082] Example 7: Based on a gradient pore structure microporous layer (PEG / C mass ratio of 100% / 50%) and a three-layer gradient catalytic layer (0.2 mg·cm³). -2Anode electrode of PtRu-10% / PtRu-20% / PtRu-60% This embodiment is based on the gradient pore structure microporous layer with a PEG / C mass ratio of 100% / 50% prepared in Example 3, and prepares 0.2 mg·cm⁻¹ microporous layer. -2 Three-layer gradient catalytic layer anode electrode.

[0083] PtRu-10wt%, PtRu-20wt%, and PtRu-60wt% catalyst slurries were prepared according to the method in Example 1. The PtRu-10wt%, PtRu-20wt%, and PtRu-60wt% catalyst slurries were sequentially sprayed onto the surface of a gradient pore structure microporous layer in ascending order of PtRu content. The PtRu-10wt% catalyst layer was located near the microporous layer, the PtRu-20wt% catalyst layer was located in the middle region, and the PtRu-60wt% catalyst layer was located near the anion exchange membrane. By controlling the spraying amount of each layer, the total PtRu noble metal loading in the anolyte catalyst layer was achieved to be 0.2 mg·cm³. -2 .

[0084] The obtained anode electrode was assembled with the Versogen A20 anion exchange membrane and the cathode electrode to form a membrane electrode assembly, and tested according to the single cell conditions described above.

[0085] As shown in Table 1 and Figure 2 , Figure 6 As shown, the test results indicate that the PtRu-10% / PtRu-20% / PtRu-60% three-layer gradient catalytic layer at 0.2 mg·cm⁻¹ exhibits good performance. -2 The catalyst exhibits superior output performance with low noble metal loading, outperforming the single PtRu-60% low-loading anode electrode in Example 5, and also superior to the PtRu-10% / PtRu-60% bilayer gradient catalyst layer in Example 6. This result indicates that the intermediate PtRu-20% catalyst sublayer can form a more reasonable transition between the low and high PtRu content layers, which is beneficial for improving the distribution of reaction sites, the continuity of electron / ion conduction, and the matching relationship of gas transport channels within the catalyst layer.

[0086] Example 8: Based on a gradient pore structure microporous layer (PEG / C mass ratio of 100% / 50%) and four gradient catalytic layers (0.1 mg·cm³). -2 Anode electrode of PtRu-10% / PtRu-20% / PtRu-30% / PtRu-60% This embodiment is based on the gradient pore structure microporous layer with a PEG / C mass ratio of 100% / 50% prepared in Example 3, and prepares 0.1 mg·cm -2 Four-layer gradient catalytic layer anode electrode.

[0087] PtRu-10wt%, PtRu-20wt%, PtRu-30wt%, and PtRu-60wt% catalyst slurries were prepared according to the method in Example 1. The PtRu-10wt%, PtRu-20wt%, PtRu-30wt%, and PtRu-60wt% catalyst slurries were sequentially sprayed onto the surface of the gradient pore structure microporous layer in order of increasing PtRu content, such that the PtRu content gradually increases from the side closest to the microporous layer to the side closest to the anion exchange membrane. By reducing the spraying amount of each layer, the total PtRu noble metal loading in the anolyte catalyst layer was controlled to be 0.1 mg·cm³. -2 .

[0088] The obtained anode electrode was assembled with the Versogen A20 anion exchange membrane and the cathode electrode to form a membrane electrode assembly, and tested according to the single cell conditions described above.

[0089] As shown in Table 1 and Figure 2 , Figure 6 As shown, the test results indicate that the noble metal loading at the anode was further reduced to 0.1 mg·cm⁻¹. -2 Even at this time, the four-layer gradient catalytic layer still maintains good battery output performance. This result indicates that the gradient catalytic layer structure described in this invention is not only suitable for 0.2 mg·cm⁻¹, but also for other applications. -2 Low-load anodes also have the potential to further reduce the amount of precious metals used.

[0090] Comparative Example 1: PtRu-60% Anode Electrode without Microporous Layer In this comparative example, an anode catalyst layer was prepared by directly spraying a PtRu-60wt% catalyst slurry onto the surface of carbon paper. The total loading of PtRu noble metal in the anode catalyst layer was controlled to be 0.6 mg·cm³. -2 0.4 mg·cm -2 and 0.2 mg·cm -2 No microporous layer was provided. The resulting anode electrode was assembled with the Versogen A20 anion exchange membrane and cathode electrode to form a membrane electrode assembly, and single-cell tests were performed under the conditions described above.

[0091] In addition, following the methods of Examples 5 to 8, 0.2 mg·cm⁻¹ was directly sprayed onto the surface of the carbon paper. -2 PtRu-60%, 0.2 mg·cm -2 PtRu-10% / PtRu-60%, 0.2 mg·cm -2 PtRu-10% / PtRu-20% / PtRu-60% and 0.1mg·cm -2The anode catalyst layer is prepared using PtRu-10% / PtRu-20% / PtRu-30% / PtRu-60% catalyst slurry, without the addition of a microporous layer.

[0092] As shown in Table 1 and Figure 1 , Figure 3 As shown in the test results, the voltage of this electrode drops rapidly under high current density, and its peak power density and limiting current density are significantly lower than those of the electrode with microporous layer. This indicates that the microporous layer plays an important role in improving anode interface contact, gas distribution and moisture removal.

[0093] Comparative Example 2: Ordinary MPL-XC72R Anode Electrode In this comparative example, an MPL-XC72R microporous layer without PEG pore-forming agent was prepared on the surface of carbon paper, and a PtRu-60wt% catalyst layer was sprayed onto its surface. The total loading of PtRu noble metal in the anode catalyst layer was controlled to be 0.6 mg·cm³. -2 0.4 mg·cm -2 and 0.2 mg·cm -2 The obtained anode electrode was assembled with a Versogen A20 anion exchange membrane and a cathode electrode to form a membrane electrode assembly, and a single-cell test was performed under the conditions described above.

[0094] In addition, an MPL-XC72R microporous layer without PEG pore-forming agent was prepared on the surface of carbon paper, and 0.2 mg·cm⁻¹ microporous layer was directly sprayed onto the surface of the carbon paper according to the methods of Examples 5 to 8. -2 PtRu-60%, 0.2 mg·cm -2 PtRu-10% / PtRu-60%, 0.2 mg·cm -2 PtRu-10% / PtRu-20% / PtRu-60% and 0.1mg·cm -2 Anode catalyst layers were prepared using PtRu-10% / PtRu-20% / PtRu-30% / PtRu-60% catalyst slurry.

[0095] As shown in Table 1 and Figure 1 , Figure 4 As shown, the test results indicate that the ordinary MPL-XC72R microporous layer can improve the anode performance to a certain extent, but its drainage capacity and high current density mass transfer performance are lower than those of the microporous layer containing PEG pore-forming agent. This suggests that the PEG pore-forming agent plays a positive role in regulating the pore structure and improving anode water management.

[0096] In summary, the results of the examples and comparative examples show that the present invention, by controlling the pore structure of the microporous layer with PEG-200 and / or PEG-400 and then heat-treating at 350 °C for 1 h under a nitrogen atmosphere to form a gradient pore structure microporous layer with a PEG / C mass ratio of 100% / 50%, can effectively enhance the anode drainage capacity and alleviate the problems of anode flooding and limited hydrogen transport under high current density. Based on this, 0.2 mg·cm³ phosphate rock can be directly prepared using a PtRu-60wt% catalyst. -2 With low anode loading, battery performance decreases compared to higher anode loading; however, by constructing a gradient loading catalyst layer using PtRu-10wt%, PtRu-20wt%, and PtRu-60wt%, performance can be improved at the same 0.2 mg·cm⁻¹. -2 The improved battery output performance under varying total precious metal loading indicates that gradient loading catalyst layers can effectively optimize the spatial distribution of precious metals and improve the utilization efficiency per unit of precious metal. Furthermore, by employing a four-layer gradient catalyst layer (PtRu-10wt%, PtRu-20wt%, PtRu-30wt%, and PtRu-60wt%), the anode precious metal loading can be further reduced to 0.1 mg·cm³. -2 The fact that the gradient pore structure microporous layer and the gradient loading catalyst layer described in this invention maintain good battery performance indicates that they have a significant synergistic effect.

[0097] The performance test results of the membrane electrodes prepared in Examples 1 to 8 and Comparative Examples 1 to 2 are shown in Table 1.

[0098] Table 1 As can be seen from Table 1, the alkaline membrane fuel cell anode electrodes prepared in Examples 1 to 8 of this invention all exhibit good cell output performance, with a peak power density of 1.56 W·cm⁻¹. -2 ~2.30 W·cm -2 The limiting current density is 4.49 A·cm. -2 ~6.10 A·cm -2 In contrast, the peak power density of the MPL-free-0.6 electrode in Comparative Example 1, which lacks a microporous layer, is only 1.59 W·cm⁻¹. -2 The limiting current density is 4.13 A·cm. -2 In Comparative Example 2, the peak power density of the PEG-0-0.6 electrode without the introduction of PEG pore-forming agent was 1.79 W·cm⁻¹. -2 The limiting current density is 5.01 A·cm. -2 The above results indicate that setting a microporous layer on the surface of carbon paper can improve anodic gas transport and interfacial contact, while further introducing PEG pore-forming agent and constructing a gradient pore structure microporous layer can significantly improve anodic drainage capacity and mass transfer performance under high current density.

[0099] Furthermore, a comparison of Examples 1, 2, and 3 shows that the PtRu loading at the anode is 0.6 mg·cm³. -2 Under these conditions, Example 1, with a PEG content of 50%, had a peak power density of 2.15 W·cm⁻¹. -2 The limiting current density is 5.25 A·cm. -2 Example 2, with 100% PEG content, had a peak power density of 2.13 W·cm⁻¹. -2 The limiting current density is 5.23 A·cm. -2 In Example 3, which employed a PEG-100% / 50% gradient pore structure microporous layer, the peak power density increased to 2.30 W·cm⁻¹. -2 The limiting current density is increased to 6.10 A·cm. -2 These results indicate that while a microporous layer with a single PEG content can improve anode drainage and gas transport, the PEG-100% / 50% gradient pore structure can better balance the drainage capacity near the carbon paper side and the structural support near the catalyst layer side, thereby further reducing anode flooding and mass transfer polarization, and improving the battery's limiting current density and peak power density.

[0100] Furthermore, a comparison of Examples 3, 4, and 5 shows that, under the condition of using a PEG-100% / 50% gradient pore structure microporous layer, as the anode PtRu loading increases from 0.6 mg·cm³, the pore size of the microporous layer decreases. -2 Reduced to 0.4 mg·cm -2 and 0.2 mg·cm -2 The peak power density is 2.30 W·cm⁻¹ -2 Reduced to 1.97 W·cm -2 and 1.56 W·cm -2 The limiting current density is 6.10 A·cm⁻¹. -2 Reduced to 5.28 A·cm -2 and 4.71 A·cm -2 Although reducing the noble metal loading leads to a decrease in battery performance, Examples 4 and 5 still maintained high output performance at lower PtRu loadings, indicating that the PEG-100% / 50% gradient pore structure microporous layer can effectively improve gas-liquid transport conditions in low-loading anodes and alleviate performance degradation caused by thinning of the catalyst layer or reduction of reaction sites.

[0101] Furthermore, a comparison of Examples 5, 6, and 7 shows that the total PtRu loading at the anode is 0.2 mg·cm³. -2Under conditions where the PEG content is 100% / 50%, the peak power density of Example 5 prepared using a single PtRu-60% catalyst is 1.56 W·cm⁻¹. -2 The limiting current density is 4.71 A·cm. -2 In Example 6, which employed a PtRu-10% / PtRu-60% bilayer gradient catalyst layer, the peak power density was increased to 2.01 W·cm⁻¹. -2 The limiting current density is increased to 4.92 A·cm. -2 In Example 7, which employed a three-layer gradient catalyst layer of PtRu-10% / PtRu-20% / PtRu-60%, the peak power density was further increased to 2.15 W·cm⁻¹. -2 The limiting current density is increased to 5.40 A·cm. -2 The above results demonstrate that, under the same low noble metal loading conditions, gradient loading catalyst layers can significantly improve the space utilization efficiency of PtRu catalysts. Specifically, the low PtRu content catalyst layer, positioned near the microporous layer, reduces the waste of noble metals in low-utilization regions far from the membrane side; the high PtRu content catalyst layer, positioned near the anion exchange membrane, ensures a high density of active sites in the membrane-side reaction region; and the intermediate PtRu-20% transition layer helps improve the distribution and transport continuity of reaction sites within the catalyst layer, thereby achieving superior low-loading battery performance.

[0102] Meanwhile, Example 8 employs a four-layer gradient catalyst layer of PtRu-10% / PtRu-20% / PtRu-30% / PtRu-60%, and further reduces the total PtRu loading at the anode to 0.1 mg·cm³. -2 1.83 W·cm can still be obtained. -2 The peak power density is 4.49 A·cm. -2 The limiting current density. This result demonstrates that the gradient pore structure microporous layer and the gradient loading catalyst layer proposed in this invention have a significant synergistic effect, not only at 0.2 mg·cm⁻¹, but also at a limiting current density. -2 It achieves output performance close to that of high-load electrodes at low loads, and has the potential to further reduce the amount of precious metals used in the anode.

[0103] In summary, this invention utilizes PEG as a pore-forming agent to regulate the pore structure of the microporous layer and employs a PEG-100% / 50% layered design to construct a gradient pore structure microporous layer, effectively enhancing anode drainage capacity and hydrogen transport capacity at high current densities. Furthermore, by sequentially spraying PtRu-10%, PtRu-20%, PtRu-30%, and PtRu-60% catalysts to construct a gradient loading catalyst layer, the spatial distribution of PtRu catalyst in the catalyst layer thickness direction can be optimized, improving the utilization efficiency of unit precious metal catalyst. These results demonstrate that this invention can maintain high peak power density and limiting current density while significantly reducing the precious metal loading at the anode, which is beneficial for achieving high performance and low cost of the anode electrode in alkaline membrane fuel cells.

[0104] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A dual-gradient low-loading film electrode, characterized in that, The dual-gradient low-loading membrane electrode comprises, from bottom to top, a gas diffusion substrate, a gradient pore structure microporous layer, and a gradient PtRu loading catalytic layer; The gradient pore structure microporous layer includes a first microporous layer and a second microporous layer arranged sequentially from bottom to top, wherein the pore size in the first microporous layer is larger than the pore size in the second microporous layer, and / or the porosity in the first microporous layer is higher than the porosity in the second microporous layer. The gradient PtRu loading catalyst layer includes a first catalyst layer and a second catalyst layer arranged sequentially from bottom to top, and the PtRu content in the first catalyst layer is less than the PtRu content in the second catalyst layer. Both the first microporous layer and the second microporous layer include conductive carbon material and pore-forming agent, wherein the mass ratio of pore-forming agent to conductive carbon material in the first microporous layer is greater than the mass ratio of pore-forming agent to conductive carbon material in the second microporous layer.

2. The dual-gradient low-loading film electrode according to claim 1, characterized in that, The mass ratio of pore-forming agent to conductive carbon material in the first microporous layer is 80%~150%; And / or, the mass ratio of pore-forming agent to conductive carbon material in the second microporous layer is 20%~80%; And / or, the conductive carbon material includes at least one of Vulcan XC-72R, acetylene black, graphitized carbon, carbon nanotubes, or graphene; And / or, both the first microporous layer and the second microporous layer further include a hydrophobic binder; And / or, the hydrophobic adhesive includes at least one of PTFE, PVDF or FEP; And / or, the pore-forming agent includes PEG-200, PEG-400, or a combination thereof.

3. The dual-gradient low-loading film electrode according to claim 1, characterized in that, Both the first and second catalyst layers include a PtRu / C catalyst and anion exchange polymer, and the mass fraction of PtRu in the first catalyst layer is less than the mass fraction of PtRu in the second catalyst layer.

4. The dual-gradient low-loading film electrode according to claim 3, characterized in that, The mass fraction of PtRu in the first catalyst layer is 10%~30%, and the mass fraction of PtRu in the second catalyst layer is 30%~60%.

5. The dual-gradient low-loading film electrode according to claim 1, characterized in that, The gradient PtRu loading catalyst layer further includes a third catalyst layer. The first catalyst layer, the second catalyst layer, and the third catalyst layer are arranged sequentially from bottom to top, and the PtRu content in the first catalyst layer, the PtRu content in the second catalyst layer, and the PtRu content in the third catalyst layer increase sequentially. The mass fraction of PtRu in the first catalyst layer is 10%~20%, the mass fraction of PtRu in the second catalyst layer is 20%~30%, and the mass fraction of PtRu in the third catalyst layer is 30%~60%.

6. The dual-gradient low-loading film electrode according to claim 1, characterized in that, The gradient PtRu loading catalyst layer further includes a third catalyst layer and a fourth catalyst layer. The first catalyst layer, the second catalyst layer, the third catalyst layer and the fourth catalyst layer are arranged sequentially from bottom to top, and the PtRu content in the first catalyst layer, the PtRu content in the second catalyst layer, the PtRu content in the third catalyst layer and the fourth catalyst layer increases sequentially. The mass fraction of PtRu in the first catalyst layer is 10%~20%, the mass fraction of PtRu in the second catalyst layer is 20%~30%, the mass fraction of PtRu in the third catalyst layer is 30%~40%, and the mass fraction of PtRu in the fourth catalyst layer is 40%~60%.

7. The dual-gradient low-loading film electrode according to claim 1, characterized in that, In the gradient PtRu loading catalyst layer, the total PtRu loading is 0.05 mg·cm³. -2 ~0.60 mg·cm -2 .

8. The method for preparing the dual-gradient low-loading film electrode according to any one of claims 1 to 7, characterized in that, Includes the following steps: Conductive carbon material, hydrophobic binder, pore-forming agent and solvent are mixed to prepare at least two microporous layer slurries with different mass ratios of pore-forming agent / conductive carbon material; A microporous layer slurry with the highest mass ratio of pore-forming agent to conductive carbon material is coated onto the surface of a gas diffusion substrate and dried to form a first microporous layer; another microporous layer slurry is coated onto the surface of the first microporous layer and dried to form a second microporous layer; the pore-forming agent is removed by heating in an inert atmosphere to form a gradient pore structure microporous layer. PtRu / C catalyst, anion exchange polymer and solvent are mixed to prepare at least two catalyst slurries with different PtRu contents; The catalyst slurry is sprayed layer by layer onto the surface of the gradient pore structure microporous layer in order of increasing PtRu mass fraction, and then dried to form a gradient PtRu loading catalyst layer, thus obtaining the dual-gradient low-loading membrane electrode.

9. A membrane electrode assembly, characterized in that, It includes an anode electrode, an anion exchange membrane, and a cathode electrode, wherein the anode electrode is the dual-gradient low-load membrane electrode as described in any one of claims 1 to 7.

10. A fuel cell, characterized in that, Includes the membrane electrode assembly as described in claim 9.

Citation Information

Patent Citations

  • Three-dimensional gradient structure anode for membrane-free oxygen-free direct methanol fuel cell and preparation method thereof

    CN109065894A

  • Gas diffusion layer for fuel cell and its preparation method

    CN1658422A